From Tax Law to Anti-Corruption Enforcement: Adapting the Una via Principle for Village Fund Corruption Cases in Indonesia - Sidi Ahyar Wiraguna (Faculty of Law, Universitas Lampung, 2025)
The una via principle, originating from European legal traditions, requires the state to choose a single enforcement mechanism administrative or criminal for the same unlawful conduct in order to avoid overlapping sanctions. In Indonesia, this principle has been formally recognized in taxation and capital market regulation, yet it remains absent in the enforcement of corruption law. This gap becomes particularly visible in cases involving village fund corruption. Empirical data from the Indonesian Attorney General’s Office between 2019 and 2023 record 1,842 cases with financial losses ranging from IDR 50 million to IDR 900 million. Despite the restoration of state losses in a significant number of cases, more than seventy percent still proceed through criminal prosecution, resulting in enforcement dualism, institutional inefficiency, and concerns regarding the proportionality of sanctions. This article argues that adapting the una via principle to corruption cases involving relatively limited losses could support a more coherent enforcement framework. Drawing on comparative experiences from the Netherlands, France, Singapore, Japan, and Malaysia, the study proposes a conditional una via model that enables prosecutors, as dominus litis, to prioritize administrative or civil recovery while maintaining criminal prosecution for more serious corruption offenses.